2020
DOI: 10.1177/1556984520971620
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Thoracoscopic Lung Resection for Non-Small-Cell Lung Cancer in Octogenarians

Abstract: Objective Octogenarians comprise an increasing proportion of patients presenting with non-small-cell lung cancer (NSCLC). This study examines postoperative morbidity and mortality, and long-term survival in octogenarians undergoing thoracoscopic anatomic lung resection for NSCLC, compared with younger cohorts. Methods We conducted a retrospective review of our institutional Society of Thoracic Surgeons General Thoracic Surgery Database of all patients ≥60 years old undergoing elective lobectomy or segmentectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…44 Thoracoscopic lung cancer resection, while minimally invasive, can still lead to complications such as arrhythmias and poor wound healing, adversely affecting postoperative recovery. 45,46 Our results shows that rapid rehabilitation nursing effectively reduces postoperative complications. The rapid rehabilitation nursing protocol involves multidisciplinary integration throughout the perioperative period, optimizing clinical pathways in preoperative preparation, nutritional care, pain management, and catheter care.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…44 Thoracoscopic lung cancer resection, while minimally invasive, can still lead to complications such as arrhythmias and poor wound healing, adversely affecting postoperative recovery. 45,46 Our results shows that rapid rehabilitation nursing effectively reduces postoperative complications. The rapid rehabilitation nursing protocol involves multidisciplinary integration throughout the perioperative period, optimizing clinical pathways in preoperative preparation, nutritional care, pain management, and catheter care.…”
Section: Discussionmentioning
confidence: 62%
“…Thoracoscopic lung cancer resection, while minimally invasive, can still lead to complications such as arrhythmias and poor wound healing, adversely affecting postoperative recovery 45,46 . Our results shows that rapid rehabilitation nursing effectively reduces postoperative complications.…”
Section: Discussionmentioning
confidence: 72%
“…Notably, prior research has directly compared the long-term prognosis between octogenarians with NSCLC who underwent surgical resection and individuals younger than 80 years, consistently showing that the elderly cohort experienced significantly poorer long-term outcomes. 10 , 13 It is believed that octogenarians may derive more significant benefits from limited lung parenchyma resection than younger individuals, and both the JCOG0802 and CALGB140503 trials have shown that sub-lobar resection mitigates respiratory function loss compared with lobectomy. 5 , 6 , 14 , 15 …”
mentioning
confidence: 99%
“…Currently, the open thoracotomy approach has been gradually replaced by minimally invasive surgery (MIS) techniques for segmentectomy and wedge resection in treating early-stage NSCLC. 13 , 17 Previous publications have shown that video-assisted thoracoscopic surgery (VATS) sub-lobar resection has many superiorities over traditional thoracotomy, including fewer postoperative complications, faster recoveries, less surgery-related pain, and better qualities of life. 13 , 18 , 19 …”
mentioning
confidence: 99%
See 1 more Smart Citation